Building student agency in rural Thailand: Using the Ikigai framework and positive youth development - Suraswadi, Pawaluk; Wichaidit, Sittichai; Polahan, Sahawarat; Brown, Gavin T. L. (Frontiers in Education, 2025)
IntroductionIt is important for life chances and schooling outcomes that students have a positive approach. The Japanese Ikigai philosophy aims at improving well-being and life purposes much as Western Positive Youth Development does. This study examined how a student positive development, based on IKIGAI, was used to develop agentic qualities in students. The study was carried out in rural Thailand where students are highly disadvantaged and experience poor schooling outcomes. The project encouraged the students to develop projects based on their own interests and contexts.MethodsContent analysis was conducted against the a priori structure of the Ikigai framework (i.e., passion, mission, profession, and vocation).ResultsData about impact were obtained from two student camps during the project and two group discussions at the end of the project from students (n = 66) in two secondary schools.DiscussionThe students gained greater passion and showed small gains in mission, profession, and vocation, with the latter two content areas only becoming visible at the end of project school discussions. The IKIGAI principles are an attractive framework for conducting youth development activities in Southeast Asia.